Impact of the convergent geometric profile on boundary layer separation in the supersonic over-expanded nozzle - Dehane, Rabie; Naima, Khatir; Liazid, Abdelkrim; İnç, Mustafa; Benarous, Abdallah; Ahmad, Hijaz; Menni, Younes (De Gruyter Poland Sp Z O O, 2022)
This article aims to conduct a numerical investigation of phenomena induced by gas expansion in chemical propulsion nozzles. A numerical simulation of full-scale flat convergent-divergent nozzle geometry using the finite volume method on structured meshes is performed to predict the change in the convergent geometry on the boundary layer separation resulting from a shock/shock and shock/boundary layer. Two turbulence models are tested, namely, the k-epsilon and k-omega shear-stress transport (SST) models. Three steps are considered to achieve this work. First, 10 numerical schemes are tested to select the accurate one. The findings of the first step are used to predict the boundary layer separation in a supersonic overexpanded nozzle. The available experimental data from the NASA Langley Research Center are used to validate the results. The third step concerns investigating the impact of the convergent geometric profile on the downstream flow of the nozzle. The obtained results are analyzed and compared with the experimental data. These results show that convergent geometry may cause the formation of different shock structures and different points of flow separation and modifies several parameters of the flow and nozzle performance downstream the throat. The findings indicated that the convergent profile must be considered during the design phase when focusing on the problem of boundary layer separation in the supersonic overexpanded regime nozzles.
Keywords: lateral load; separation criterium; shock tube; plan convergent divergent nozzle; Riemann problem